2010
DOI: 10.1177/0093650210362678
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Impact of Attachment Style on Evaluations of Supportive Messages: A Dual-Process Framework

Abstract: This article reports tests of hypotheses derived from a theory of supportive message outcomes that maintains that the effects of supportive messages are moderated by factors influencing the motivation and ability to process these messages. Participants ( N = 331) completed measures of attachment style, which provided individual-level assessments of processing motivation, and responded to either a mildly or moderately severe problem, which manipulated situational motivation.They subsequently evaluated the helpf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
3
31
0
2
Order By: Relevance
“…These studies informed the adaptation of dual-process models of persuasion to account for the influence of supportive communication on recipients (Bodie & Burleson, 2008;Bodie et al, 2011;Burleson, 2009). The dual-process approach suggests that message content has its strongest effect on outcomes when receivers engage in in-depth message processing, and it recognizes that support receivers use their cognitive resources to process messages thoroughly only when they are able and motivated to do so (Bodie, 2011).…”
Section: Processing Supportive Messagesmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies informed the adaptation of dual-process models of persuasion to account for the influence of supportive communication on recipients (Bodie & Burleson, 2008;Bodie et al, 2011;Burleson, 2009). The dual-process approach suggests that message content has its strongest effect on outcomes when receivers engage in in-depth message processing, and it recognizes that support receivers use their cognitive resources to process messages thoroughly only when they are able and motivated to do so (Bodie, 2011).…”
Section: Processing Supportive Messagesmentioning
confidence: 98%
“…As noted previously, the majority of studies of VPC support messages have examined people's immediate perceptions of messages (see Bodie et al, 2011;Burleson, 2008;Jones & Burleson, 1997) or improvement in affect after exposure to comforting messages (Jones, 2004;Jones & Burleson, 2003). Two studies that did examine over-time effects of support conveyed in a conversation investigated a time frame of less than one hour.…”
Section: Longitudinal Outcomes For Support Recipientsmentioning
confidence: 99%
“…Pretests were conducted in order to (a) ensure that HPC messages were perceived as more person‐centered than LPC messages and (b) verify that the support exchange situation was relatively low in severity. The rationale for a less severe situation is that lower‐severity problems are less likely to prompt central processing of support messages, elevating the influence of heuristic (source) qualities in message processing (e.g., see Bodie et al, ; Burleson, , Study 3). Because this research was interested in the effects of overt heuristic cues, a situation in which such cues were important provided a more useful test of hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…Four categories of attachment styles have been described by the literature: secure, avoidant, ambivalent or resistant, and disorganized (Berlin et al, 2008;Bodie et al, 2011). Infants with a secure attachment style tend to believe that their needs will be met and are generally happy, secure, and explorative at baseline.…”
Section: Attachment Stylementioning
confidence: 99%
“…Individuals who have experienced past negative events, which they find difficult to decathect, may have developed an anxiety attachment style as a result of these negative or traumatic events. Anxiety attachment style in adults is usually characterized by difficulty with the ability to trust people, fear of abandonment and disappointment, difficulty with the ability to be alone, fear of the loss of a love object, and fear of death and annihilation (Bodie et al, 2011;Bowlby, 1979;Thompson, 2008). Zimbardo and Boyd (1999) found that individuals with past-negative time perspectives had unsatisfactory and minimal interpersonal relationships and reported having fewer close friendships as compared to those with other time perspectives.…”
Section: Resilience Predicted Future (+)mentioning
confidence: 99%